Estimation of the average sample size and defective ratio In a finite individualized inspection with a practical application - جاسم اسامة محمد (Journal of Economics and Administrative Sciences, 2009)
The purpose of this research is to find the estimator of the average proportion of defectives based on attribute samples. That have been curtailed either with rejection of a lot finding the kth defective or with acceptance on finding the kth non defective. The MLE (Maximum likelihood estimator) is derived. And also the ASN in Single Curtailed Sampling has been derived and we obtain a simplified Formula All the Notations needed are explained.